Resilient yet productive: maize that can thrive under stress and in optimal conditions - Das, Reshmi Rani; Vinayan, Madhumal Thayil; Seetharam, Kaliyamoorthy; Ahmad, Salahuddin; Thaitad, Suriphat; Nguyen, Thanh; Patel, Manish B.; Phagna, Ramesh Kumar; Lenka, Devraj; Zaidi, Pervez H. (Frontiers in Plant Science, 2025)
In the Asian tropics, maize is predominantly grown as a rainfed crop during the summer-rainy season, which often suffers significant yield losses due to the erratic distribution pattern of monsoon rain that causes intermittent dry spells and/or excessive moisture within the season. The climate-induced abiotic stresses, particularly drought and waterlogging, pose significant threats to rainfed maize cultivation in the Asian tropics, where erratic patterns of monsoon rain and associated high genotype-by-environment interaction (GEI) effects undermine yield stability. To address these challenges, this study evaluated 61 advanced-stage maize hybrids developed under the Asia Waterlogging and Drought Tolerant (AWDT) product profile, designed to deliver hybrids with stable grain yields under variable moisture regimes without yield penalties under optimal conditions. Multi-environment trials (METs) were conducted across 19 locations in South and Southeast Asia (India, Bangladesh, Vietnam, and Thailand) under four moisture regimes: optimal, rainfed/random stress, reproductive-stage drought, and vegetative-stage waterlogging. A stratified ranking approach was employed to identify superior hybrids that matched or exceeded commercial checks under optimal conditions and outperformed them under at least one stress environment. Several elite hybrids demonstrated broad or specific adaptation to targeted stress-prone environments. These findings underscore the importance of targeted breeding and MET-based selection strategies in developing high-performing stress-resilient maize cultivars for climate-vulnerable agroecologies, with implications for food security, farmer livelihoods, and sustainable cropping systems in the face of escalating climate variability.